Memahami Etika Politik Kontemporer - Muhammad Fardhannajmi; Muhammad Rizky Darmawan; Rayhan Noor; Surya Sukti (Indo Publishing, 2026)
This study examines the relationship between ethics and politics as fundamental dimensions of human social life, emphasizing their role in shaping just and responsible governance. Ethics, as a branch of philosophy, provides moral principles that guide human behavior, while politics functions as the practical sphere in which power, decision-making, and public policies are exercised. The study explores classical and modern perspectives, including Aristotle’s view of the unity of ethics and politics in achieving the highest good, Machiavelli’s pragmatic approach that separates morality from political necessity, and Kant’s insistence on universal moral principles in political action. Furthermore, the discussion extends to contemporary political ethics, highlighting key issues such as justice, human rights, transparency, accountability, and the influence of digital technology. The ideas of John Rawls and Jürgen Habermas are examined to demonstrate the importance of fairness, equality, and participatory dialogue in modern governance. Central to this study is the concept of the common good, which serves as a core political value aimed at ensuring collective welfare and social justice. The study concludes that ethics and politics are inherently interconnected and must be integrated to prevent the misuse of power and to promote inclusive and equitable governance. A strong ethical foundation, supported by democratic institutions and active public participation, is essential for realizing the common good in contemporary society.